Strategi Pengembangan Perguruan Islam Daarul Muwahhidiin Tanah Datar sebagai Lembaga Pendidikan Islam Berwawasan Global - Latifah, Hafidah Dinatul; Asmira, Asmira; Despatriani, Despatriani; Emelia, Rita; Asmendri, Asmendri; Sari, Milya (LP2M Universitas Islam Ahmad Dahlan, 2023)
As times become increasingly sophisticated, Islamic educational institutions must be able to adapt to these developments. To be able to adapt to all developments over time, Islamic educational institutions must develop their institutions into Islamic educational institutions with a global perspective. The step that needs to be taken is to develop a strategy so that the Islamic educational institution becomes an Islamic educational institution with a global perspective. Based on this phenomenon, researchers are interested in finding out the strategy of one Islamic educational institution, namely the strategy for developing Daarul Muwahhidiin Islamic Boarding School as an Islamic educational institution with a global perspective. The method used in this research is a type of qualitative research with a descriptive approach. The research was conducted for 2 months starting from September to October with 23 respondents. The data sources obtained in this research are divided into two, namely from the results of field studies or observations and literature studies or library research from various sources. The results of this research are the strategies for developing Daarul Muwahhidiin Islamic Boarding School as an Islamic educational institution with a global perspective.